2023
DOI: 10.1038/s41380-023-02269-8
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional serotonergic neuron-astrocyte signaling in depressive-like states

Candela González-Arias,
Andrea Sánchez-Ruiz,
Julio Esparza
et al.

Abstract: Astrocytes play crucial roles in brain homeostasis and are regulatory elements of neuronal and synaptic physiology. Astrocytic alterations have been found in Major Depressive Disorder (MDD) patients; however, the consequences of astrocyte Ca2+ signaling in MDD are poorly understood. Here, we found that corticosterone-treated juvenile mice (Cort-mice) showed altered astrocytic Ca2+ dynamics in mPFC both in resting conditions and during social interactions, in line with altered mice behavior. Additionally, Cort-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 145 publications
0
8
0
1
Order By: Relevance
“…Ketamine has been shown to drive monoaminergic signaling to elevate NE and 5-HT in the extracellular space 16,62 , and, in the case of serotonin 74 , this elevation has been shown to be important to mediate antidepressant-like effects of ketamine in rodents. Astrocytes have been shown to respond to elevations in NE 2124,38 and serotonin 31 with elevations in cytosolic calcium. Furthermore, astroglial responsiveness to serotonin has recently been shown to be disrupted in rodent depression models, and stimulating prefrontal cortex astrocytes chemogenetically has been shown to rescue depression-related behavioral phenotypes 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketamine has been shown to drive monoaminergic signaling to elevate NE and 5-HT in the extracellular space 16,62 , and, in the case of serotonin 74 , this elevation has been shown to be important to mediate antidepressant-like effects of ketamine in rodents. Astrocytes have been shown to respond to elevations in NE 2124,38 and serotonin 31 with elevations in cytosolic calcium. Furthermore, astroglial responsiveness to serotonin has recently been shown to be disrupted in rodent depression models, and stimulating prefrontal cortex astrocytes chemogenetically has been shown to rescue depression-related behavioral phenotypes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes have been shown to respond to elevations in NE 2124,38 and serotonin 31 with elevations in cytosolic calcium. Furthermore, astroglial responsiveness to serotonin has recently been shown to be disrupted in rodent depression models, and stimulating prefrontal cortex astrocytes chemogenetically has been shown to rescue depression-related behavioral phenotypes 31 . Ketamine has also been shown in vitro to decrease astroglial calcium responses to stimuli like ATP and to attenuate calcium-coupled secretion of chemical messengers by astroglia 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, revelation of the importance of astrocyte Ca 2+ signaling in homeostatic control of brain circuits and behavior has led to the suggestion of potential exploitation of this system in MDD treatment [179] [180]. Further understanding of astrocyte-neuron involvement in MDD pathology including the alterations of mid-spiny neurons and pyramidal neurons, as well as the alterations of gliotransmitters between astrocytes and neurons could provide novel targets in MDD [181].…”
Section: Astrocytes -Depressionmentioning
confidence: 99%
“…Note that, in this study, we showed no effect of the GFAP cell ablation or activation on anxiety-like behaviors, which may oppose the findings previously discussed, where optogenetics or acute chemogenetics were employed. A concomitant recent study by González-Arias et al [ 188 ] investigated PFC GFAP+ cell activity in juvenile mice subjected to chronic corticosterone treatment and showed impairments of astroglial activity during tests measuring anxiety or social interaction deficits that were reversed in mice by chronic chemogenetic enhancement of GFAP+ cell activity. Another study used chronic chemogenetic activation to investigate astroglial modulation of alcohol consumption [ 189 ].…”
Section: Effect Of Astrocyte Manipulations On Emotion-related Behaviormentioning
confidence: 99%